2009
DOI: 10.1098/rspb.2009.0087
|View full text |Cite
|
Sign up to set email alerts
|

Social implications of the battle of the sexes: sexual harassment disrupts female sociality and social recognition

Abstract: Across sexually reproducing species, males and females are in conflict over the control of reproduction. At the heart of this conflict in a number of taxa is male harassment of females for mating opportunities and female strategies to avoid this harassment. One neglected consequence that may result from sexual harassment is the disruption of important social associations. Here, we experimentally manipulate the degree of sexual harassment that wild female guppies (Poecilia reticulata) experience by establishing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 42 publications
1
46
2
Order By: Relevance
“…In fact, in social animals, sexual coercion may have its main impact on females because of its potential to disrupt the dynamics of social interactions, as shown in this and other studies [3,6,9]. In socially grouping species, affiliative and agonistic behaviours are central to the maintenance of group structure and collective group behaviour [19].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In fact, in social animals, sexual coercion may have its main impact on females because of its potential to disrupt the dynamics of social interactions, as shown in this and other studies [3,6,9]. In socially grouping species, affiliative and agonistic behaviours are central to the maintenance of group structure and collective group behaviour [19].…”
Section: Discussionmentioning
confidence: 87%
“…In addition, it is increasingly becoming apparent that the presence of sexually harassing males directly affects female social behaviour [4][5][6][7][8]. In a recent study, Darden et al [6] found that male sexual behaviour may in fact be detrimental to female sociality, with female Trinidadian guppies (Poecilia reticulata) showing fragmentation of social networks and a decreased propensity to develop social recognition based on familiarity with other females in their environment. There is suggestive evidence in mammals that harassing males affect fission-fusion properties of groups of females [3] and female-female levels of aggression [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The behavioural strategy investigated here is an example of how individuals take this into account in their social partner decisions, in a sexual conflict setting. The results underline that female responses to sexual harassment can have profound consequences for social structure [41,42]. Association decisions based on sexual attractiveness may well be widespread in other species with high levels of harassment.…”
Section: Discussionmentioning
confidence: 83%
“…Another potential cost is the disruption of social networks and interactions among females, which is an important consequence of sexual harassment in guppies (Poecilia reticulata) (Darden, James, Ramnarine, & Croft, 2009). The potential for similar social consequences of coercion in primates has not been studied directly.…”
Section: Costs Of Sexual Coercionmentioning
confidence: 99%